School Health Unit as Main Facility for Health Development in the School - Asvio, Nova; Yusup, Muhammad; Astuti, Andri; Nurhikmah, Nurhikmah; Anwar, Khairul (Yayasan Sembilan Pemuda Indonesia, 2022)
This study aims to describe the school health unit (UKS) as the main facility of health development in the Elementary School 79 Bengkulu. This research is conducted by using a qualitative approach and case study design. The sources of research data got from the principal, homeroom teacher, physical education teacher, and UKS custodian. This study uses observation techniques, interviews, and documentation. The stages of data analysis used Data Reduction Analysis Techniques, Data Presentation, and Conclusions. The results showed that UKS functions as the main facility for healthy development for students at elementary school, UKS conducted counseling on the importance of personal hygiene to students, UKS introduced a healthy environment and various diseases, and managed and implemented UKS facilities.